THE USING OF LOGISTIC TOOLS FOR EFFECTIVE USE OF THE TRANSIT POTENTIAL OF UKRAINE - Dykan, Ye. V. (Science and Transport Progress, 2008)
Development of transit, logistics and containerization characterizes the state of the modern national transport system. Thus the development of one of directions, for example transit, has served by a stimulus to expansion of process of cargo containerization, and this, in its turn, has forced to think about building of container terminals. For this reason the problems of transit, logistics and containerization must be considered in a complex. In the article the attempt to select separate directions is done.